Faktor Determinan Mempengaruhi Kunjungan dan Loyalitas Wisatawan ke Destinasi Wisata Berkelanjutan Tanjung Karang di Kabupaten Donggala - Suparman Suparman; Agus Susanto; I Gusti Putu Diva Awatara (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the influence of tourist motivation and perceived quality on tourist loyalty, with tourist satisfaction as a mediating variable at the Tanjung Karang sustainable tourism destination in Donggala Regency, Central Sulawesi. The research approach used is a quantitative explanatory approach, with a population of all tourists visiting the Tanjung Karang destination during the period of July–September 2025. The research sample consisted of 70 respondents, determined through a purposive sampling technique. While data analysis used Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results of this study found that perceived quality was proven to be the main determinant of tourist satisfaction. This result emphasizes the importance of improving facilities, cleanliness, and local community services. Tourist satisfaction has a direct influence on loyalty, confirming that positive experiences are the basis for forming revisit intentions. Tourist motivation did not have a significant effect on satisfaction or loyalty, indicating that psychological drives are not strong enough without the support of good service quality. Satisfaction was proven to mediate the influence of motivation and perceived quality on loyalty, according to the expectation-confirmation theoretical framework and the Motivation–Satisfaction–Loyalty model.